Chrysothallite K6Cu6Tl3+Cl17(OH)4·H2O, a new mineral species from the Tolbachik volcano, Kamchatka, Russia. (2nd January 2018) - Pekov, Igor V.; Zubkova, Natalia V.; Belakovskiy, Dmitry I.; Yapaskurt, Vasiliy O.; Vigasina, Marina F.; Lykova, Inna S.; Sidorov, Evgeny G.; Pushcharovsky, Dmitry Yu.
Abstract: A new mineral chrysothallite K6 Cu6 Tl 3+ Cl17 (OH)4 ·H2 O was found in two active fumaroles, Glavnaya Tenoritovaya and Pyatno, at the Second scoria cone of the Northern Breakthrough of the Great Tolbachik Fissure Eruption, Tolbachik volcano, Kamchatka, Russia. Chrysothallite seems to be a product of the interactions involving high-temperature sublimate minerals, fumarolic gas and atmospheric water vapour at temperatures not higher than 150ºC. It is associated with belloite, avdoninite, chlorothionite, sanguite, eriochalcite, mitscherlichite, sylvite, carnallite and kainite at Glavnaya Tenoritovaya and with belloite, avdoninite, chlorothionite, eriochalcite, atacamite, halite, kröhnkite, natrochalcite, gypsum and antlerite at Pyatno. The mineral forms equant-to-thick tabular crystals up to 0.05 mm, typically combined in clusters or crusts up to 1 mm across. Crystal forms are: {001}, {100}, {110}, {101} and {102}. Chrysothallite is transparent, bright golden-yellow to light yellow in finely crystalline aggregates. The lustre is vitreous. The mineral is brittle. Cleavage was not observed, the fracture is uneven. D meas = 2.95(2), D calc = 2.97 g cm –3 . Chrysothallite is optically uniaxial (+), ω = 1.720(5), ε = 1.732(5). The Raman spectrum is given. The chemical composition (wt.%, electron-microprobe data, H2 O calculated based on the crystal structure data) is: K 15.92, Cu 24.56, Zn 1.38, Tl 13.28, Cl 40.32, H2 O(calc.) 3.49, total 98.95. The empirical formula, calculated on the basis of 17 Cl + 5 O a.p.f.u., is: K6.09 (Cu5.78 Zn0.32 )Σ6.10 Tl0.97 Cl17 [(OH)3.80 O0.20 ]·H2 O. Chrysothallite is tetragonal, I 4/ mmm, a = 11.3689(7), c = 26.207(2) Å, V = 3387.3(4) Å 3, Z = 4. The strongest reflections of the powder X-ray pattern [ d, Å ( I )( hkl )] are: 13.20(44)(002); 6.88(100)(112); 5.16(30)(202, 114); 4.027(25)(220); 3.471(28)(206), 3.153(30)(314), 3.075(47)(305), 2.771(38)(316). The crystal structure (solved from single-crystal X-ray diffraction data, R = 0.0898) is unique. Its basic structural unit is a (001) layer of edge-sharing distorted CuCl4 (OH)2 octahedra. Two Tl 3+ cations occupy the centre of isolated TlCl6 and TlCl4 (H2 O)2 octahedra connected to each other and to the Cu polyhedral layers via KCl6 and KCl9 polyhedra. The name reflects the bright golden-yellow colour of the mineral (from the Greek χρυσος, gold) and the presence of thallium. Chrysothallite is the second known mineral with species-defining trivalent thallium.